2019
DOI: 10.1016/j.psychres.2018.12.108
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum total cholesterol is associated with a history of childhood physical violence in depressed outpatients

Abstract: Decreased serum total cholesterol is associated with a history of childhood physical violence in depressed outpatients, Psychiatry Research (2018), doi: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…This founding is consistent with previous studies reporting the lower fatty acid levels might be related to violence [23,59]. Although earlier studies have reported the serum cholesterol, a subclass of lipid [60], is uncorrelated with violence [61,62], more recent studies have consistently found the increased violence risk is correlated with low cholesterol concentration [19,20,63] and polyunsaturated fatty acid [26,59]. Omega-3 supplement can reduce violent behaviours in children [25], young men [64], schizophrenia patients [26] and adult prisoners [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This founding is consistent with previous studies reporting the lower fatty acid levels might be related to violence [23,59]. Although earlier studies have reported the serum cholesterol, a subclass of lipid [60], is uncorrelated with violence [61,62], more recent studies have consistently found the increased violence risk is correlated with low cholesterol concentration [19,20,63] and polyunsaturated fatty acid [26,59]. Omega-3 supplement can reduce violent behaviours in children [25], young men [64], schizophrenia patients [26] and adult prisoners [23].…”
Section: Discussionsupporting
confidence: 89%
“…Earlier studies reported glycine mediates the defend reaction types in mouse behaviours [18]. In addition, low levels of cholesterol associated with aggression are frequently reported [19][20][21][22]. Recently, many studies have found dietary omega-3 supplementation can reduce violent behaviours in children, young men and schizophrenia patients [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…More recently Deschênes et al (2018) reported that ACEs are indirectly associated with diabetes via depressive symptoms and cardio-metabolic dysregulations. The most recent study found decreased TC levels in adult outpatients with MDD with a childhood history of physical violence (Kraav et al, 2019). The same study found no differences in serum levels of HDL-C and LDL-C between the groups (Kraav et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study found decreased TC levels in adult outpatients with MDD with a childhood history of physical violence (Kraav et al, 2019). The same study found no differences in serum levels of HDL-C and LDL-C between the groups (Kraav et al, 2019). In our present study, we could detect higher serum triglyceride and lower HDL-cholesterol levels in MDD patients who experienced childhood adversity compared to MDD patients without ELS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation